Case report: Monoclonal CGRP-antibody treatment in a migraine patient with a mutation in the mitochondrial single-strand binding protein (SSBP1) - Kaltseis, Katharina; Indelicato, Elisabetta; Broessner, Gregor; Boesch, Sylvia (Frontiers in Neurology, 2022)
Background There is a growing body of mitochondrial disorders that are associated with headaches, albeit only one of them is currently listed in the latest International Classification of Headache Disorders, 3rd edition (ICHD-3). Headache frequency and headache presentation can vary widely in this respective patient group. Acute and preventive migraine treatment can be quite challenging—the use of several established medications is often limited due to their side effects in the setting of mitochondrial dysfunction and multi-organ disease. Case presentation Along with a review of the literature on treatment options in patients with mitochondrial disorders and migraine headaches, we present the case of a 23-year-old male with a homozygous mutation in the mitochondrial single-strand binding protein (SSBP1) with chronic migraine with aura. After failing several standard of care prophylactics due to either side effects or inefficacy, he was successfully treated with a monoclonal anti-CGRP-antibody as a preventive migraine treatment. The monoclonal antibody was well tolerated and showed adequate efficacy with a sustained > 50% reduction in monthly headache days after 3 years of treatment. Conclusion Migraine is often challenging to treat in patients with mitochondriopathy due to therapy-limiting comorbidities. Monoclonal CGRP-antibodies might be a safe treatment option in the prevention of migraine headaches in patients with a mitochondrial disorder.